Studies on Fecundity of a Hill Stream Loach Noemacheilus montanus (McClelland) in Relation to Total Length, Total Weight, Ovary Length and Ovary Weight - Bahuguna, S.N.; Khatri, S. (Our Nature, 2010)
A total of forty mature specimens of Noemacheilus montanus collected from river Alaknanda and its tributaries ranging from 7.0 cm to 9.2 cm in length and from 2.31 g to 5.49 g in weight were used for the present study. The fecundity was calculated to be 500 to 1005. The relationships between fecundity and total length, total weight, ovary length and ovary weight were found to be linear. The coefficient of correlation ‘r’ for the above relationships was found to be 0.948, 0.906, 0.909 and 0.969 respectively. Key words: Noemacheilus montanus, Hill Stream Loach, Fecundity, Alaknanda river, Ovary length DOI: 10.3126/on.v7i1.2558 Our Nature (2009) 7:116-121